PTH-334 Cost-effectiveness of warm humidified co2 to reduce surgical site infections in laparoscopic colorectal surgery: a cohort study. (22nd June 2015) - Mason, SE; Kinross, JM; Reynecke, D; Hendricks, J; Arulampalam, TH
Abstract : Introduction: Surgical Site Infections (SSI) are a common complication which negatively impact on patient quality of life and constitute a financial burden to healthcare providers. The objective of this study is to evaluate whether using warmed, humidified carbon dioxide for peritoneal insufflation decreases the incidence of SSIs, improves patient safety and provides value for money. Method: A retrospective cohort study of patients undergoing elective laparoscopic colorectal resection for both benign and malignant disease was performed at a single UK specialist centre from September 2012 to July 2014. The control group (n = 126) received peritoneal insufflation with standard cold, dry carbon dioxide whereas the intervention group (n = 126) received peritoneal insufflation with warmed, humidified carbon dioxide (using HumiGard TM, Fisher&Paykel Healthcare). All patients had standard prophylactic antibiotic therapy on induction. The primary outcome measures were incidence of SSI and costs (standard-of-care costs, intervention costs and SSI treatment costs incurred at an average cost of £2000 per SSI). The intervention was assessed by calculating the Risk Ratio (RR), Odds Ratio (OR) and incremental cost-effectiveness ratio (ICER) per infection-free patient gained. Results: Median age was 68 (20–87). The median BMI was 27 (SD 5.98). The mean operation time was 211 min (SD 92.7), M:F ratio was 1:1. The primary diagnoses were as follows: cancer n = 174, diverticulitis n = 31, Crohn's n = 15, ulcerative colitis n = 10, other n = 22. There was no significant variation in age, BMI, sex, smoking status, operation time or conversion rates between groups. Introduction of warmed, humidified carbon dioxide for peritoneal insufflation reduced the incidence of SSI from 12% to 4.7% (RR = 0.40; p = 0.049; 95% CI: 0.160 – 0.997 and OR = 0.37; p = 0.047; 95% CI = 0.138 – 0.987). Treatment costs including SSI costs for patients in the control group amounted to approximately £31000 compared to £21500 in the intervention group. The ICER for the intervention is -£1226, the negative number indicating a net reduction in costs in addition to decreased SSI incidence. It costs on average £1226 less to generate each additional infection-free patient using the intervention. Conclusion: This study indicates that warmed, humidified carbon dioxide is superior to cold, dry carbon dioxide for peritoneal insufflation in laparoscopic colorectal surgery. The intervention appears to be cost-effective whilst decreasing surgical morbidity. Disclosure of interest: None Declared.